Ildefonsa z Toledo modlitwy do Matki Bożej. Analiza treści modlitw - Wygralak, Paweł (Vox Patrum, 2023)
The paper presents an analysis of two prayers by Ildefonso of Toledo addressed to Mary contained in the work “De virginitate Sanctae Mariae”. Both the very personal form of the prayers and their content deserve attention. In these prayers, the Bishop of Toledo expresses his deepest feelings towards Mary, describing her as his Lady and Sovereign. He praises her for her participation in the work of salvation, but above all he asks her intercession so that he can be united with Christ. In doing so, he indicates what true Marian devotion consists of: it should always lead to a deepening of the relationship with Christ.